Coordination‐Cage‐Catalysed Hydrolysis of Organophosphates: Cavity‐ or Surface‐Based?. Issue 14 (6th February 2020) - Taylor, Christopher G. P.; Metherell, Alexander J.; Argent, Stephen P.; Ashour, Fatma M.; Williams, Nicholas H.; Ward, Michael D.
Abstract: The hydrophobic central cavity of a water‐soluble M8 L12 cubic coordination cage can accommodate a range of phospho‐diester and phospho‐triester guests such as the insecticide "dichlorvos" (2, 2‐dichlorovinyl dimethyl phosphate) and the chemical warfare agent analogue di(isopropyl) chlorophosphate. The accumulation of hydroxide ions around the cationic cage surface due to ion‐pairing in solution generates a high local pH around the cage, resulting in catalysed hydrolysis of the phospho‐triester guests. A series of control experiments unexpectedly demonstrates that—in marked contrast to previous cases—it is not necessary for the phospho‐triester substrates to be bound inside the cavity for catalysed hydrolysis to occur. This suggests that catalysis can occur on the exterior surface of the cage as well as the interior surface, with the exterior‐binding catalysis pathway dominating here because of the small binding constants for these phospho‐triester substrates in the cage cavity. These observations suggest that cationic but hydrophobic surfaces could act as quite general catalysts in water by bringing substrates into contact with the surface (via the hydrophobic effect) where there is also a high local concentration of anions (due to ion pairing/electrostatic effects). Abstract : Magic 8‐ball : An octanuclear cubic coordination cage host binds organophosphate guests in the central cavity as the crystal structure of the complex with the insecticide 'dichlorvos' shows; but catalysed hydrolysis in aqueous solution occurs primarily at the external surface and not in the cavity.